2015
DOI: 10.1021/acs.macromol.5b01240
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thin Film Confinement on Surface Plasticity in Polystyrene and Poly(2-vinylpyridine) Homopolymer and Block Copolymer Films

Abstract: Thin block copolymer films have attracted considerable academic attention because of their ability to self-assemble into various microstructures, many of which have potential technological applications. Despite the ongoing interest, little effort has focused on the onset of plasticity and failure which are important factors for the eventual adoption of these materials. Here we use delamination to impart a quantifiable local stain on thin films of homopolymer polystyrene and poly(2-vinylpyridine), as well as bl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…11,40 To date, only the tensile modulus and crack-onset strain can be extracted easily from FOE systems, whereas previous methods for measuring the yield point are substantially more complex and limited to certain types of polymers. 17,18 Other properties relevant to mechanical reliability in flexible devices, such as adhesion and cohesive fracture energy, can also be obtained from thin films in other configurations. 29,30 Figure 2 illustrates the information easily obtainable from FOE systems superimposed on a hypothetical stress−strain curve obtained from a conventional pull tester.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…11,40 To date, only the tensile modulus and crack-onset strain can be extracted easily from FOE systems, whereas previous methods for measuring the yield point are substantially more complex and limited to certain types of polymers. 17,18 Other properties relevant to mechanical reliability in flexible devices, such as adhesion and cohesive fracture energy, can also be obtained from thin films in other configurations. 29,30 Figure 2 illustrates the information easily obtainable from FOE systems superimposed on a hypothetical stress−strain curve obtained from a conventional pull tester.…”
Section: Introductionsupporting
confidence: 76%
“…In addition to the effect of alkyl side-chain length, we explored the effects of film thickness on the yield point. Others had previously shown that decreasing film thickness depresses the glass transition temperature of thin films, and we hypothesized that this would lead to an increase in yield point in P3ATs, as has been shown for polystyrene and poly­(2-vinylpyridine) using a relatively complex method. , Our goal was thus to develop a simple procedure to measure the yield point using similar equipment, an actuator, a laser, and a microscope, to those already used routinely to measure tensile modulus and crack-onset strain.…”
Section: Introductionmentioning
confidence: 99%
“…The roughness of the surface topography of the submicron PS- b -P2VP dots reflects the nanoporous-spongy nature of the sacrificial PS- b -P2VP stamps. The crazing behavior of thin PS- b -P2VP films has been reported to be complex. , Nevertheless, we assume that the following aspects promote the rupture of the contact elements.…”
Section: Resultsmentioning
confidence: 92%
“…Figure 3a reported to be complex. 40,41 Nevertheless, we assume that the following aspects promote the rupture of the contact elements. in thin PS homopolymer films have been reported to be less entangled than in the bulk, corresponding to a confinement-induced increase in M c .…”
Section: Sacrificial Stampingmentioning
confidence: 99%
See 1 more Smart Citation